Cascading effects of thermally-induced anemone bleaching on associated anemonefish hormonal stress response and reproduction - Ricardo Beldade (Nature Portfolio, 2017)
Elevated temperatures can cause anemones to bleach, with unknown effects on their associated symbiotic fish. Here, Beldade and colleagues show that climate-induced bleaching alters anemonefish hormonal stress response, resulting in decreased reproductive hormones and severely impacted reproduction.